On an atomic decomposition in Banach spaces - Telman Gasymov; Chingiz Hashimov (Sahand Communications in Mathematical Analysis, 2018)
An atomic decomposition is considered in Banach space.  A method for constructing an atomic decomposition of Banach  space, starting with atomic decomposition of  subspaces  is presented. Some relations between them are established. The proposed method is used in the  study  of the  frame  properties of systems of eigenfunctions and associated functions of discontinuous differential operators.